2020
DOI: 10.1080/22423982.2020.1788339
|View full text |Cite
|
Sign up to set email alerts
|

“When I feel well all over, I study and learn better” - experiences of good conditions for health and learning in schools in the Arctic region of Sweden

Abstract: A challenge facing the Arctic region is the disengagement of both education and work among its youth. Only by supporting young people who are struggling with mental and physical health challenges can we begin to address this societal challenge. Education, mental health and social inclusion are prominent factors for future employment, income and independent living for young people. The aim of this study was to describe and understand the experiences of good conditions for health and learning in schools in the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
1
0
0
Order By: Relevance
“…Based on the findings, the health dialogues can help schools to reach the full potential in promoting students’ health literacy and learning when a whole-school approach is used to build enabling relationships among all school staff and students. This is in accordance with earlier research (Adamowitsch et al, 2017; Kostenius & Nyström, 2020). Warne et al (2017) also argue for a whole-school approach in which students’ sense of belonging is strengthened.…”
Section: Discussionsupporting
confidence: 94%
“…Based on the findings, the health dialogues can help schools to reach the full potential in promoting students’ health literacy and learning when a whole-school approach is used to build enabling relationships among all school staff and students. This is in accordance with earlier research (Adamowitsch et al, 2017; Kostenius & Nyström, 2020). Warne et al (2017) also argue for a whole-school approach in which students’ sense of belonging is strengthened.…”
Section: Discussionsupporting
confidence: 94%
“…The findings, especially from qualitative studies (see Kostenius and Nyström, 2020;Quenzel and Ott, 2023), suggest that active co-design in the classroom and in teaching can also promote student well-being (H 4 ). Hammerin et al (2018) showed a positive relationship between active participation in teaching and a reduced stress experience among students.…”
Section: Discussion Of the Results In Light Of The Hypothesesmentioning
confidence: 99%
“…Although students reported that they felt better when they could actively participate in the classroom, they also said that they felt more stressed because they had to make decisions themselves. Additionally, Kostenius and Nyström (2020) showed in their qualitative survey that active participation in school-similar to active co-design as the top rung of Hart's participation ladder-contributes to greater health well-being. Overall, the results suggest that adolescents who are involved in and able to shape decision-making processes in their schools and classes may feel better.…”
Section: Shared Decision-making Processmentioning
confidence: 99%
“…Open-ended surveys were used to allow participants to voice their experiences after they were invited to use the ChatPal chatbot, make suggestions and give their opinions. This cooperative and participatory approach with young people is echoed in the body of work on student voice [ 14 , 38 ]. The COREQ checklist developed by Tong et al [ 39 reporting standards to help to enhance the transparency of qualitative research is added as an appendix ( Appendix 1 ).…”
Section: Methodsmentioning
confidence: 99%